Estudios sobre el funcionamiento de vehículos inteligentes - Pigott, Mary (2025)
With the approval of the new United States Transportation Equity Act for the 21st Century (TEA-21), which includes the 1998 initiative to study intelligent vehicles, the U.S. Department of Transportation has undertaken various research efforts aimed at reducing crash-related incidents by up to 17% of the total 1.1 million accidents recorded annually.